Description of Single and Multi-Valued Semantic Words “Discrimination” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Even due to the fact that the bulk of commonly used words are polysemous, the study of polysemy, rather than monosemy as a linguistic phenomenon, acquires greater theoretical and practical significance. In particular, the study of polysemantic aspects of discriminatory semantic words lays the foundation for a more accurate manifestation of their lexical properties. Because when a token is implemented in speech, the question of what meanings it means is very relevant.